Proceedings of the 5th Nordic Conference on Human-Computer Interaction: Building Bridges 2008
DOI: 10.1145/1463160.1463205
|View full text |Cite
|
Sign up to set email alerts
|

Designing and evaluating the tabletop game experience for senior citizens

Abstract: In this paper, we report on the design and evaluation of a tabletop game especially created for senior citizens. The game is intended to provide leisure and fun and is played with four players on an augmented tabletop. It evolved from existing games and rules that are popular and familiar amongst senior citizens. Several aspects that are part of the gaming experience, such as immersion, flow, affect and, challenge, were assessed experimentally. The gaming experience was measured relatively by subjectively comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 8 publications
1
35
0
3
Order By: Relevance
“…The augmented dancing environment DanceAlong by Keyani et al [15] also addresses the issue of physical activity among senior citizens, aiming to motivate seniors to engage in dancing along with popular movie scenes. Another study found that playing brain-training games on a portable game console had a positive correlation with reported fun for an elderly age group (compared to a younger control group) suggesting cognitive challenges provide a satisfying gameplay mechanic for the elderly [19]. Finally, the ElderGames project by Gamberini et al [7] presents a tabletop gaming solution specifically designed to test and train cognitive abilities of elderly persons.…”
Section: Related Workmentioning
confidence: 99%
“…The augmented dancing environment DanceAlong by Keyani et al [15] also addresses the issue of physical activity among senior citizens, aiming to motivate seniors to engage in dancing along with popular movie scenes. Another study found that playing brain-training games on a portable game console had a positive correlation with reported fun for an elderly age group (compared to a younger control group) suggesting cognitive challenges provide a satisfying gameplay mechanic for the elderly [19]. Finally, the ElderGames project by Gamberini et al [7] presents a tabletop gaming solution specifically designed to test and train cognitive abilities of elderly persons.…”
Section: Related Workmentioning
confidence: 99%
“…This video recording technique was used by some researchers such as [16][17][18], while the use of screen footage is intended to see the exploration or exploration activities of users used by researchers such as [19][20].…”
Section: Experimental Designmentioning
confidence: 99%
“…Furthermore, digital tabletop games have been designed to meet the needs of an elderly audience. Mahmud et al [15] found that senior citizens primarily enjoy simple card games such as poker and designed a tabletop game in which players have to draw cards in order to move checkers on a projected grid. ElderGames [9] is a table-based digital game for elderly users that combines game elements with cognitive challenges and sensomotor training.…”
Section: Systems For Elderly Gamersmentioning
confidence: 99%